2000
DOI: 10.2514/2.5692
|View full text |Cite
|
Sign up to set email alerts
|

Hub-Based Vibration Control of Multiple Rotating Airfoils

Abstract: A study of vibration control of rotating airfoils using hub-based actuators (speci cally, magnetic bearings) is presented. A simulation model consisting of a shaft/bladed disk assembly supported by two radial magnetic bearings and a thrust bearing is used to investigate the effectiveness and limitationsof such an approach. Aerodynamic effects are accounted for with a simple model, and controllable vibrationmodes are determined. Deliberate patterned blade mistuning is identi ed as a possible strategy to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, if properly mistuned it was shown that the disk becomes controllable. Numerical control results of a mistuned disk controlled via shaft-based actuation were described in the work [11] and in [9,10]. The controllability analysis was based on a study of only time-invariant mode shapes while the time-variant vibration modes, known as parametric modes, which will occur due to vibration coupling between rotor and blades, were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…However, if properly mistuned it was shown that the disk becomes controllable. Numerical control results of a mistuned disk controlled via shaft-based actuation were described in the work [11] and in [9,10]. The controllability analysis was based on a study of only time-invariant mode shapes while the time-variant vibration modes, known as parametric modes, which will occur due to vibration coupling between rotor and blades, were not considered.…”
Section: Introductionmentioning
confidence: 99%